The Biophysical Modelling of Transport Phenomena and of Crossing-Effects in Living Organisms - Vincze, Janos; Gabriella Vincze-Tiszay, (British Journal of Healthcare and Medical Research, 2023)
The transport phenomena mean the variation in time and space of generalized forces when they generate flows for which conservation laws apply. After we describes: mass-, impulse-, energy- and electric-charge-transport and their mathematical characteristic equations. From the biophysiscal study are well-known the next laws: diffusion, viscosity, thermal conductibility, and electric conductibility. In the living organisms, flows are not generated only by the conjugated generalized forces, but also by the simul¬taneous action of other forces, so frequencies of the crossing-effects in the human organism. The biophysical modelling uses very frequently the general laws of isomorphisms. Through modelling, we can find the system’s transfer function (the way the system acts upon the entry size) or when it is known, the entry size can be found. The modelling of some bio-medical systems eases the analysis of the processes which take place in that particular original and allow the study of their action in the conditions which are difficult or even impossible to organize. The biophy¬sical modeling offer a. language” of quantitative and qualitative processing of experimental data, being compatible and adequate to the laws of biology.